PERANCANGAN APLIKASI MEDIA INFORMASI DAN PEMESANAN BERBASIS WEB UNTUK COFFEE SHOP TEMPAT BERCERITA - Resnu Rifnaldy; Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Application of Web-Based Information and Ordering Media for Coffee Shops, Places to Tell Stories, was created as a promotional media container from the store and also to make it easier for customers to place orders, as well as help the store to process order data properly. The process of designing this application uses the Waterfall model System Development Life Cycle (SDLC) development methodology. The programming languages used are HTML and PHP. The database used in this application is MySQL. The purpose of Designing a Web-Based Information and Ordering Media Application for a Coffee Shop where Tells stories is so that Places can easily manage online order data and be able to market their products more broadly.